(untitled) (Journal of Forest and Livelihood, 2013)
Reducing Emission from Deforestation and Forest Degradation (REDD) is an incentive based approach for climate change mitigation that has gained global attention. Following the global discourse and trend, Nepal is preparing herself to participate in the REDD implementation process with the financing from the World Bank’s Forest Carbon Partnership Facility (FCPF). Developing a measurement, reporting and verification (MRV) system of monitoring carbon emissions is one of the most important aspects of the REDD mechanism. In this article, we analyse the existing forest resource monitoring system in Nepal with reference to requirements for the REDD MRV design as suggested in the Intergovernmental Panel on Climate Change (IPCC) good practice guide. Our analytical focus revolves around understanding the current policy provisions and institutional infrastructure, as well as identifying existing gaps Similarly, we also analyse the national capacity gaps for designing and adopting the REDD MRV. Finally we have outlined possible issues and challenges for designing and implementing REDD MRV in Nepal. Based on all these aspects, we have suggested a MRV system design that would acknowledge the role of existing institutions and consider the state restructuring. DOI: http://dx.doi.org/10.3126/jfl.v9i1.8591 Journal of Forestry and Livelihood Vol.9(1) 2010 21-32